Hiprogaed / Mohammad Haziq Mohammad Jainal … [et al.] - Mohammad Jainal, Mohammad Haziq; Azhar, Mufeed Imran; Norazmi, Faris Aiman Minhaj; Idris, Muhammad Irham Izzudidin; W. Salleh, W. Ahamad Azran; Othman, Hidayatulfathi; Mohd Rashid, Muhammad Zarif; Amiruddin, Nurul Fitri Asyikin; Jamel, Nabila; Rawlinson, Rachel Selalang; Idiris, Omar Syabil (Division of Research and Industry Linkages, 2017)
Commonly either in rural or city areas, mosquito infestation has spread at a maximum stage. To overcome this problem our team has conducted a research with getting the help from Dr Hidayatulfathi Othman, Universiti Kebangsaan Malaysia and came out with this superb product HIProGAed (High Protection Against Aedes). This is an effective and user friendly mosquito repellent lotion made from aromatic herb extract. The specialty of our product is that it gives a more convenience approach in repelling mosquitoes. The product also enables user to move freely while still have protection, compared to the usual mosquito coil, which is not suitable for home use and children. This is an organic based, allowing safe and harmless usage on even infants and children. HiProGAed protects skin from mosquito, because the aroma/scent from lotion makes mosquitoes uncomfortable. Our target market are parents with children and infants as they are more vulnerable and exposed to mosquito attacks.